Cyberspace, distance learning, and higher education in developing countries : old and emergent issues of access, pedagogy, and knowledge production - Assié-Lumumba, N'Dri Thérèse (International studies in sociology and social anthropology ;, 2004)
Annotation Amidst the euphoria about the new frontiers of technology sometimes perceived as a panacea for expansion of higher education in developing countries, there is a need to analyze persistent and new grounds of unequal opportunity for access, learning, and the production of knowledge. This volume addresses fundamental questions about the educational process such as: 7 The use of technology in higher education for a holistic educational system for social development7 The actual technological capacity in Africa and possibilities for virtual higher education7 Cultural relevance of the curriculum and pedagogy7 Pedagogy and gender in cyberspace education7 Perils of externally-driven distance education programs in Africa and the quest for ownership towards development7 Challenges and opportunities in the making of knowledge society in an Asian context7 Strategies to promote constructive virtual higher education in Africa and Asia.